1997
DOI: 10.1055/s-2007-1004154
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Esophageal Wallstent and Ultraflex Stents in the Treatment of Malignant Stenoses of the Esophagus and Cardia

Abstract: Compared to Ultraflex stents, Wallstents have several significant short-term and long-term advantages in the palliative treatment of malignancy of the esophagus and cardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Recurrent dysphagia being the leading symptom of stent dysfunction has been observed in this study and by others in as many as 50% of patients during a follow-up of 4-10 weeks [10,11]. Recanalization procedures such as laser therapy or further stent insertion, but also systemic chemotherapy and radiation seem to be of major importance to prolong stent patency [4,[6][7][8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 68%
“…Recurrent dysphagia being the leading symptom of stent dysfunction has been observed in this study and by others in as many as 50% of patients during a follow-up of 4-10 weeks [10,11]. Recanalization procedures such as laser therapy or further stent insertion, but also systemic chemotherapy and radiation seem to be of major importance to prolong stent patency [4,[6][7][8][9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 68%
“…Unfortunately, fatal complications such as perforation and massive hemorrhage occurred frequently [4,13]. In recent years, self-expanding metallic stents have been developed for the palliative treatment of malignant stenoses caused by unresectable esophageal cancer [1,2,[6][7][8]11]. These metallic stents have become more popular than conventional plastic stents because they are associated with a lower incidence of complications [5,10].…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy revealed that the stent had perforated into the mediastinal pleura and that an abscess had developed around the perforation. We conclude that caution should be taken before combining radiation therapy with the use of a stent.In patients with advanced unresectable esophageal cancer, self-expanding metallic stents are regarded as effective palliation for dysphagia [1,2,[6][7][8]11]. These stents have several merits, including infrequent complications, a low incidence of procedure-related mortality, and shorter hospital stays than those for patients receiving conventional rigid plastic stents [5,10].…”
mentioning
confidence: 99%
“…Additionally, perforations could also be observed with the occurrence of fistulae into surrounding tissue. Esophago-mediastinal fistulae have shown severe complications such as pneumothorax [4] and aortic erosion [2] with lethal hemorrhages.…”
Section: Discussionmentioning
confidence: 99%